English Peer Counseling to Engage Students’ Speaking Confidence and Motivation in Higher Education - Farid Noor Romadlon (AL-ISHLAH: Jurnal Pendidikan, 2022)
Textbook-based teaching commonly used in the ELT context in Indonesia results in a hard stimulation for students to speak more since the focus is reading skills. Activating peers' activities through English peer counselling in teaching speaking is one of the effective ways to promote students’ confidence and motivation in speaking. It is an activity conducted by peers that focuses on developing fundamental skills, especially speaking. This research aims to know the students' thoughts about English peer counselling toward their confidence and motivation in speaking. This research is qualitative research with a case study design. The researcher used a questionnaire as an instrument to collect the data. The questionnaire was given to 115 students of the English Education Program who joined the activity. The result shows that the first indicator reached 58,1%, which belongs to the neutral category. In comparison, the second indicator reached 91,4%. The final score for indicator one and indicator two was 79,8%. It indicates that students positively perceive English peer counselling to engage their speaking confidence and motivation. The activity encourages students to be more active in small conversations and discussions. They have better confidence in talking to their peers, which also gains their motivation. Similar research about English peer counselling for different skills, e.g. reading, writing, and listening, is highly possible to conduct.